Indicators for national consumption-based accounting of chemicals. (1st April 2019) - Persson, L.; Arvidsson, R.; Berglund, M.; Cederberg, C.; Finnveden, G.; Palm, V.; Sörme, L.; Schmidt, Sarah; Wood, Richard
Abstract: Increased chemical use is causing a growing number of environmental problems and chemical products are pervasive in societies within animal and crop-based agriculture, in industrial processes and in households. National environmental targets, as well as the global chemical-related goals in the 2030 Agenda, call for the monitoring of chemical use and emissions. The growing international trade of goods, where use and regulation of chemical inputs vary highly between countries, complicates measurements. This paper addresses these issues by deriving a set of indicators on chemical use and emissions and connect the global impacts to a country's total consumption, here using the case of Sweden. The indicators are based on a hybrid model combining the multi-regional input-output analysis database EXIOBASE with data from the Swedish System of Economic and Environmental Accounts together with a novel set of environmental extensions. A review of databases is conducted and discussed in relation to the driver-pressure-state-impact-response (DPSIR) framework for indicators. Five indicators are calculated, showing the chemical use and emissions connected to consumption, both within a country and abroad. The indicators are: use of hazardous chemical products, use of pesticides, use of antimicrobial veterinary medicines, emissions of hazardous substances, and of the potential toxicity of these emissions. The results show that the impact of Swedish consumption in terms of use and emissions of hazardous substances is largely taking place outside the Swedish borders. Only 10–24% of the pressure from Swedish consumption is shown to occur within Sweden's borders, depending on the indicator. The use of hazardous chemical products and veterinary medicines related to Swedish consumption primarily takes place in other EU countries, whereas the use of pesticides as well as reported emissions of pollutants occur mainly in countries outside the EU. The results highlight the need for improved international accounting of chemical flows, as well as for strengthened policy frameworks to address cross-border impacts of consumption of hazardous chemical products.